2021
DOI: 10.1021/acs.cgd.1c00910
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Quantum Dots as Nucleants for Protein Crystallization

Abstract: Structural analysis of proteins using X-ray crystallography is crucial for discovering their biochemical functionalities. However, growing X-ray-quality crystals of proteins is often a challenging task that requires complicated and tedious processes, especially for the formation of crystalline seeds in the early stage of the process. In the present study, graphene quantum dots (GQDs) were investigated as a nanomaterial nucleant for protein crystallization in the aspects of the process accelerations and their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
(74 reference statements)
1
5
0
Order By: Relevance
“…The crystal formed at such conditions is considered to exhibit a tetragonal morphology [21][22][23][24]. As stated in other works, no significant effect on the structure of lysozyme crystals was discovered when nanoparticles such as gold particles or carbon quantum dots (GQDs) were used as nucleating agents [12,25]. Therefore, it is speculated here that the addition of nanoparticles may not alter the lysozyme crystal assembly process and that the lysozyme crystals obtained belong to a tetragonal morphology.…”
Section: Effect Of Snp Sizes On Lysozyme Crystal Morphologymentioning
confidence: 87%
“…The crystal formed at such conditions is considered to exhibit a tetragonal morphology [21][22][23][24]. As stated in other works, no significant effect on the structure of lysozyme crystals was discovered when nanoparticles such as gold particles or carbon quantum dots (GQDs) were used as nucleating agents [12,25]. Therefore, it is speculated here that the addition of nanoparticles may not alter the lysozyme crystal assembly process and that the lysozyme crystals obtained belong to a tetragonal morphology.…”
Section: Effect Of Snp Sizes On Lysozyme Crystal Morphologymentioning
confidence: 87%
“…32,33 ILs, MIPs, and DESs are important additives having more effective properties which are different from those of traditional additives, such as degradability and designability. Some other additives have been reported for protein crystallization, such as graphene quantum dots, 45 carbon-nanotube-based materials, 46 and rough well surfaces. 47 There are detailed reviews of this subject.…”
Section: Additivesmentioning
confidence: 99%
“…It has been reported that nanomaterials in the form of aggregates or films could improve the crystallization efficiency of all proteins [ 58 , 59 ]. Nanodiamond (ND) is a kind of carbon-based nanomaterial that has extensive biological application potential [ 60 ]. One such application is to promote the nucleation of protein crystals in aqueous solutions ( Figure 5 ) [ 59 ].…”
Section: Heterogeneous Nucleating Agentsmentioning
confidence: 99%